Numerical Study of EV Frame Performance in Side Pole Collision: ASTM A36 vs. AL-7075T6 Analysis - Mukhlis Amin; Bahatmaka, Aldias Bahatmaka (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
Electric vehicles are emerging as eco-friendly alternatives to reduce greenhouse gas emissions and combat global warming. The Indonesian government supports this transition through subsidies, infrastructure development, and regulations encouraging electric vehicle adoption. Automotive manufacturers are enhancing electric vehicle models with safer and more efficient technology. Ensuring the frame's durability during collisions is crucial for safety. Structural engineering plays a vital role, as material failure from operational loads or impacts can lead to significant losses. The large and heavy batteries in electric vehicles present challenges in designing frames that support loads while maintaining passenger safety. Side-pole crash testing is essential due to the limited crumple zones on vehicle sides. This study analyzed the performance of ASTM A36 and AL-7075T6 materials in a side-pole collision at 32 km/h speed using the Finite Element Analysis method. The results showed that both materials experienced almost the same deformation, 98.79 mm for ASTM A26 and 98.77 mm for AL-7075T6. It is, however, a large difference in the maximum stress, ASTM A36 at 4849.7 MPa, and AL-7075T6 at only 1699.9 MPa. This was shown that AL-7075T6 has a better impact resistance than ASTM A36, therefore increasing the safety of electric vehicle frames for side-pole collision conditions.